Validation of self-reported periodontal disease status among subjects seeking dental treatment in a dental school - Khalid Gufran; Mohammed Alasqah; Sultan Almalki; Yousef Alkhaibari; Yazeed Alghamdi; Tariq Z Aljulify (Wolters Kluwer Medknow Publications, 2020)
Introduction: Periodontal disease and its relation with quality of life have made it necessary to know in detail regarding the disease. Hence, the aim of this study was to check the validity of self-reported periodontal status with clinical findings among subjects attending a dental teaching institution. Materials and Methods: A cross-sectional study was conducted on subjects with periodontitis attending a dental teaching institution. A questionnaire was developed after reviewing the relevant literature and participants were asked to complete the questionnaire. Information about signs and symptoms of periodontal disease was included, and subjects were examined for periodontal disease. Data were recorded and analyzed for sensitivity and specificity. Result: A total of 103 subjects answered the study questionnaire and underwent clinical examination. The sensitivity of question varied from 16.6% with need of periodontal or gum treatment to 57.1% in case of gingival swelling. In many questions, more than 90% of specificity was found. There was a difference in self-assessed periodontal status with clinically examined periodontal status. Conclusion: Self-assessed questionnaires were of low value in evaluating oral periodontal disease status. Periodontal perception of subjects was higher but does not reflect with clinical findings; this calls for educational programs to be conducted to improve knowledge and awareness about periodontal diseases.